Table of Content - -, (Journal of Educational and Psychological Sciences, 2023)
Table of Content:1. Strategic leadership and its role in achieving organizational justice in private Yemeni universities from the point of view of academic and administrative leadersMrs. Fatima Mohammed Maqbool Qaiqab , Co-Prof. Abdulaziz Abdul Hadi Al-Amri2. The Practicing Degree of Early Elementary Grades' Teachers for Creative Thinking Skills from Their Point of ViewMrs. Mariah Abdullah Alshammari, Dr. Mansour Muzil Alanazi3. The role of the mother in the scientific formation of her children in the light of Islamic educational thought Imam Malik bin Anas as a modelDr. Abeer Muhammad Aljufair4. The Psychometric properities of the online teaching competencies scale among faculty members at Umm Al-Qura UniversityMrs. Eptehal Zakaria Hafiz5. Building a training program to develop the performance of kindergarten teachers and measuring its impact on developing the Speaking skills of kindergarten children for the Republic of YemenMrs. Zakiah Mohammed Ali Al-Jamrah6. Educational Implications of the Winter Season's Provisions in the Light of Islamic EducationMrs. Mashael Raja Alhizan , Mrs. Rasha Ghazi Matar , Mrs. Hanna Hamed Aljuhani , Mrs. Belqes Mohammed Ahmed Atya7. The Orientation Towards Helping Others and its Relationship with Emotional Awareness among University Students.Mrs. Hanan Hussein Ibrahim Shaaban , Co-Prof. Iyad Grace Al-Shawareb8. Psychological Hardiness and its Relation to Social Networking Sites Addiction among a Sample of Female Adolescents in JeddahMrs. Sara Naif Mansoor , Co-Prof. Radyah Mohammed Hamidaddin
Keywords: Journal of Educational and Psychological Sciences